Pendidikan Karakter Berbasis Wawasan Nilai-Nilai Pondok Pesantren: Character Education Based on the Values and Insights of Islamic Boarding Schools - M. Ahyar Ma'arif; Ani Purwatiningsih (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2016)
Globalization has led to a decline in moral values, patriotism, and Indonesia's national character, making character education an urgent priority. Islamic boarding schools (pesantren), as a subsystem of national education, possess noble values that can serve as a foundation for character building. This study aims to describe the character education values based on pesantren insights and their implementation strategies. Using a qualitative case study approach at Raudlatul Jannah Islamic Boarding School, data were collected through observation, interviews, and documentation. The findings reveal that the five core principles of pesantren—sincerity, simplicity, self-reliance, Islamic brotherhood, and regulated freedom—serve as the spirit of character education. Implementation is carried out through role modeling, habituation, advice, and reward and punishment systems over a full 24-hour period. In conclusion, pesantren values are effective in shaping students' character toward insan kamil, and it is recommended that this system be adaptively adopted by general educational institutions. Globalisasi telah menyebabkan kemerosotan nilai moral, patriotisme, dan karakter bangsa Indonesia, sehingga pendidikan karakter menjadi agenda mendesak. Pondok pesantren, sebagai sub-sistem pendidikan nasional, memiliki nilai-nilai luhur yang dapat dijadikan landasan pembentukan karakter. Penelitian ini bertujuan untuk mendeskripsikan nilai-nilai pendidikan karakter berbasis wawasan pesantren dan strategi implementasinya. Penelitian ini menggunakan pendekatan kualitatif dengan studi kasus di Pondok Pesantren Raudlatul Jannah melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menemukan bahwa lima jiwa utama pesantren yaitu keikhlasan, kesederhanaan, kemandirian, ukhuwah Islamiyah, dan kebebasan bertanggung jawab menjadi ruh pendidikan karakter. Implementasinya dilakukan melalui keteladanan, pembiasaan, nasihat, serta pemberian hadiah dan hukuman selama 24 jam penuh. Kesimpulannya, nilai-nilai pesantren efektif membangun karakter santri menuju insan kamil, dan direkomendasikan agar sistem ini diadopsi secara adaptif oleh lembaga pendidikan umum.